CHEMICAL AND MICROBIOLOGICAL STATUS OF COW DUNG AND COW URINE OF DESI AND HF BREED IN DAIRY FARM OF ZAHRS, BABBUR FARM, HIRIYUR - A. H. KUMAR NAIK; S.UMESHA; B. M. MADHU (The Bioscan, 2020)
A laboratory experiment was undertaken in the Zonal Agricultural and Horticultural research station, Babbur farm, Hiriyur with view to know the nutrient contents and microbial load in dung and urine of Hallikar and HF breeds cow. The Hallikar cow dung and urine were noticed highest amount of nutrient viz., N, P and K (0.81 and 1.10, 018 and 0.22, 0.61 and 1.04 %) and highest number of viable microorganisms viz., bacteria (79.33 and 51.33 x 10 5 ), fungi (4 x 10 4 ), actinobacteria (18 x 10 3 ), N 2 - fixers (48 and 22 x 10 5 ), P-solubilizers (7.33 and 2.0 x 10 5 ), Pseudomonas sp. (66 x 105) respectively as compared to dung and urine of HF cow breed. The fungal, actinobacteria, Pseudomonas sp. and Trichoderma sp. growth were not observed in cow urine sample.